UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Kusdinar, Deden (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on the author's experience teaching for this in SD Negeri 010 Banjar PanjangKerumutan, and based on observation and early reflections by the author seen low creativityof students in learning that ultimately ends up in the low student learning outcomesthemselves, especially on the subjects of Natural Sciences. After many tests on the midtermturns lower student learning outcomes. Completeness class only reach 50% or 10 out of 20students, KKM for subjects of Natural Sciences which has been set in the class IV SD Negeri010 Banjar Panjang Kerumutan is the number 70. As Judge things that cause children lowvalue, from the aspect of teachers are: teacher always using methods lectures, learningachievement of children have been considered equally by teachers, and the learning processis dominated by the teacher. This research is a classroom action research (PTK). Class actionresearch through the stages of planning, implementation, observation and reflection. Fromthe research data is a result of learning of natural science at the top can be seen learningoutcome science students from the action on the preliminary data for the first cycle to thesecond cycle by improving student learning outcomes that menigkat are significant, the initialdata of students who achieve mastery only 50 % and cycle to the first increase has reached70% and the thoroughness of the class in the second cycle reaches 85%.